Acute Traumatic Epidural Hematoma in Geriatri, case report - Aulia Agung Sanubari; Dety Nirbhita; Geizar Arsika R (Publikasi Indonesia, 2024)
Acute epidural haematomas (AEDH) are rare cases in geriatric age group as the dura adheres firmly to the inner table of the cranial bone. Trauma Brain Injuries are attributed to several mechanisms of injury, including falls, motor vehicle or other types of road injuries, sports-related injuries, and interpersonal physical violence or violence by other means (e.g., blast injury). Presentation may range widely from normal mental status to severe intracerebral injury in the elderly although acute deterioration may occur in previously conscious patients. There are only a few studies in the literature concerning acute epidural haematomas in geriatric age group. In our case, a 66-year-old male patient with cranial Computerized Tomography (CT) showed AEDH at the right parietotemporooccipital region.